2017
DOI: 10.1089/neu.2016.4693
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury and Post-Deployment Binge Drinking among Male and Female Army Active Duty Service Members Returning from Operation Enduring Freedom/Operation Iraqi Freedom

Abstract: This study examines whether the relationship between traumatic brain injury (TBI) and post-deployment binge drinking is independent of screening positive for mental health problems among male and female service members. Data are from the Substance Use and Psychological Injury Combat Study of Army members returning from deployment to Afghanistan or Iraq in fiscal years 2008-2011. The sample consists of 240,694 male and 26,406 female active duty members who completed initial and follow-up questionnaires. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 51 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…Among young veterans, the prevalence of binge drinking among males is nearly twice that of their female counterparts (43.2% vs. 22.9%) (SAMHSA, 2010). Consistent with these findings, the prevalence of frequent binge drinking among male soldiers returning from deployment is 3 times that of females (21.2% vs. 7.4%) (Sayko Adams et al, 2017). Other research in non-US military samples also suggests that male military personnel are significantly more likely to have problems with alcohol than their female counterparts (Waller et al, 2015).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Among young veterans, the prevalence of binge drinking among males is nearly twice that of their female counterparts (43.2% vs. 22.9%) (SAMHSA, 2010). Consistent with these findings, the prevalence of frequent binge drinking among male soldiers returning from deployment is 3 times that of females (21.2% vs. 7.4%) (Sayko Adams et al, 2017). Other research in non-US military samples also suggests that male military personnel are significantly more likely to have problems with alcohol than their female counterparts (Waller et al, 2015).…”
Section: Introductionmentioning
confidence: 64%
“…Given the gaps identified in the literature and emerging evidence on the well-being of never-deployed service members, the goal of this study was to examine the potential relations between non-deployment emotions and a range of alcohol use outcomes among a sample of male and female never-deployed USAR/NG soldiers. We also aimed to explore the interactions between non-deployment emotions and sex on these alcohol outcomes, given the difference in drinking behaviors between male and female service members (SAMHSA, 2010, Sayko Adams et al, 2017, Waller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks connecting these areas of the prefrontal cortex to the basal ganglia and midbrain constitute the reward circuit, which have been implicated in substance abuse (Casement, Shaw, Sitnick, Musselman, & Forbes, 2014;Forbes, Rodriguez, Musselman, & Narendran, 2014). Specifically, damage to the orbital frontal cortex has been associated with reduced ability to control impulsive behavior (Sellitto, Ciaramelli, & di Pellegrino, 2010), which may influence self-regulation of substance use (Adams, Corrigan, Mohr, Williams, & Larson, 2017). We propose that TBI can have unrecognized consequences that may increase the risk for opioid use disorders (OUD).…”
mentioning
confidence: 99%
“…Three retrospective cohort studies reported on alcohol use among active duty service members or veterans with a history of TBI ( n = 19 240; 6.0% female; n = 30 197; 6.1% female; n = 402; 7.0% female). In all three, male veterans engaged in risky drinking behaviors at significantly higher rates than female veterans.…”
Section: Resultsmentioning
confidence: 99%